2010
DOI: 10.1007/s00535-010-0291-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of long-term ezetimibe therapy in patients with nonalcoholic fatty liver disease

Abstract: The results in this study suggest that the long-term EZ therapy can lead to improvement in metabolic, biochemical, and histological abnormalities of NAFLD. Therefore, EZ may be a promising agent for treatment of NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
117
1
6

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 170 publications
(131 citation statements)
references
References 46 publications
7
117
1
6
Order By: Relevance
“…Third, the average serum aminotransferase levels were lower than those in previous studies [9,10], and most of the patients had mild steatosis, fibrosis and lower NAS at baseline before ezetimibe treatment. Serum ALT levels did not decrease with ezetimibe treatment in the present study, in contrast to the significant improvement reported previously [9,10]. And finally, secondary outcomes are always at risk of false-positive associations.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Third, the average serum aminotransferase levels were lower than those in previous studies [9,10], and most of the patients had mild steatosis, fibrosis and lower NAS at baseline before ezetimibe treatment. Serum ALT levels did not decrease with ezetimibe treatment in the present study, in contrast to the significant improvement reported previously [9,10]. And finally, secondary outcomes are always at risk of false-positive associations.…”
Section: Discussionmentioning
confidence: 62%
“…Indeed, a 6 month duration may be too short a period to expect improvement of fibrosis, which is a slowly ND, not determined progressive process [40]. Third, the average serum aminotransferase levels were lower than those in previous studies [9,10], and most of the patients had mild steatosis, fibrosis and lower NAS at baseline before ezetimibe treatment. Serum ALT levels did not decrease with ezetimibe treatment in the present study, in contrast to the significant improvement reported previously [9,10].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…77,101 The newer agent ezetimibe, which acts through inhibiting cholesterol absorption, has shown promising effects, especially in association with acarbose, but further results are needed in order to enable its use to be validated as a current recommendation. [111][112][113][114] There is a lack of conclusive evidence supporting the use of ursodeoxycholic acid, N-3 polyunsaturated fatty acids, angiotensin receptor blockers, probiotics and synbiotics as validated treatment options for NAFLD.…”
Section: 107-110mentioning
confidence: 99%
“…Studies have explored ezetimbe monotherapy or in combination with other agents such as statins and acarbose, which in general, showed improvement in aminotransaminases and lipid profile and NAS on histology. However, there was no significant effect on fibrosis [76,77]. A subsequent and only RCT to date that evaluated ezetimibe in NAFLD with post treatment histology reported significant improvement in histological ballooning and fibrosis from baseline, but there were no significant histological differences compared to placebo.…”
Section: Lipid Lowering Agentsmentioning
confidence: 97%